PENGARUH KINERJA KEUANGAN ENTITAS DAN FAKTOR LAINNYA TERHADAP AUDIT DELAY - Velia Findriani; Rudi Setiadi Tjahjono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to determine the influence of the entity’s financial performance and other factors to audit delay. The examined factors are profitability, solvability, liquidity, company size, audit opinion, public accounting firm's size, audit tenure and audit committee. Population in this research is non-financial companies listed in Indonesian Stock Exchange with research period from 2017-2019. the sampling is selected by a purposive sampling method and there were 165 companies that meet the sample criterias from the total population of 420 companies. The multiple regression analysis was applied to this research..The result of this research identified profitability, company size, audit opinion has influenced on audit delay. This means that a better financial performance of the entity and a fairly audit opinion (unqualified opinion) will accelerate the timing of audit completion. Conversely, for other variable, solvability, liquidity, public accounting firm's size, audit tenure and audit committee has no influence to audit delay.